Front Cover: Pillararene‐Based Two‐Component Thixotropic Supramolecular Organogels: Complementarity and Multivalency as Prominent Motifs (Chem. Eur. J. 59/2018). Issue 59 (16th September 2018) - Zafrani, Yossi; Kaizerman, Dana; Hadar, Maya; Bigan, Nitzan; Granot, Eran; Ghosh, Moumita; Adler‐Abramovich, Lihi; Patolsky, Fernando; Cohen, Yoram
Abstract : Supramolecular organogels are an intriguing family of stimuli responsive soft materials. The present study describes a rationally designed thixotropic two‐component supramolecular organogel based on multiple chemical interactions between percarboxylato‐ and peramino‐pillar[5]arenes. The most significant result of this study is the exceptional combination of properties that these supramolecular organogels have, namely, they display thixotropy, low minimal gelation concentration (MGC), very high thermal stability, and unique thermal behavior. These supramolecular organogels appear to have pentagonal nanotubular molecular core structures. More information can be found in the Communication by Y. Zafrani, Y. Cohen et al. on page 15750 .